Dyslipidaemia in HIV-infected women on antiretroviral therapy. Analysis of 922 patients from the Spanish VACH cohort - Estrada Vicente; Geijo Paloma; Fuentes-Ferrer Manuel; Alcalde María; Rodrigo María; Galindo María; Muñoz Agustín; Domingo Pere; Ribera Esteve; Cosín Jaime; Viciana Pompeyo; Lozano Fernando; et al. (BMC Women's Health, 2011)
Abstract Background Information concerning lipid disturbances in HIV-infected women on antiretroviral therapy (ART) is scarce. The objective of the study is to describe the lipid profile in a large cohort of HIV-infected women on contemporary ART and analyse differences between regimes and patient's characteristics. Methods Observational, multicentre, cross-sectional study from the Spanish VACH Cohort. 922 women on stable ART without lipid-lowering treatment were included. Results Median age was 42 years, median CD4 lymphocyte count was 544 cells/mm3, and 85.6% presented undetectable HIV-1 viral load. Median total cholesterol (TC) was 189 mg/dL (interquartile range, IQR, 165-221), HDL cholesterol 53 mg/dL (IQR, 44-64), LDL cholesterol 108 mg/dL (IQR, 86-134), and triglycerides 116 mg/dL (IQR, 85-163). Mean accumulated time on ART was 116 months; 47.4% were on NNRTI-based regimes, 44.7% on PI, and 6.7% on only-NRTI therapy. 43.8% were also hepatitis C (HCV) coinfected. Patients on PI treatment presented higher TC/HDL ratio than those on NNRTI (p < 0.001). Significantly higher HDL values were observed in NNRTI-treated patients. HCV-coinfected patients presented lower TC/HDL ratio than the non HCV-coinfected. In multivariate analysis, factors independently associated with TC/HDL ratio were age, triglyceride levels and HCV co-infection. PI treatment presented a non-significant association with higher TC/HDL ratio. Conclusions In HIV-infected women, the NNRTI-based ART is associated with a better lipid profile than the PI-based. Factors unrelated to ART selection may also exert an independent, significant influence on lipids; in particular, age, and triglyceride levels are associated with an increased TC/HDL ratio while HCV co-infection is associated with a reduced TC/HDL ratio.